Bioinspired polymers for lubrication and wear resistance. (November 2020) - Adibnia, Vahid; Mirbagheri, Marziye; Faivre, Jimmy; Robert, Jordan; Lee, Jeungjun; Matyjaszewski, Krzysztof; Lee, Dong Woog; Banquy, Xavier
Abstract: In this review, we discuss the concept of bioinspired lubrication using novel polymeric structures, which has led to producing a myriad of new systems with effective and sustainable antifriction and wear resistant properties. Therefore, three classes of polymeric materials are analyzed: (i) modified naturally-occurring polymeric thin film coatings, which have been recently introduced as effective lubricants and wear resistant materials; (ii) synthetic polymeric thin film coatings, most of which owe their excellent lubrication and wear resistant properties to their biomimetic structures; (iii) hydrogels and elastomers as soft solid substrates with modified chemistries and structures that have enhanced their lubrication and wear resistant properties. The latter class is typically used as artificial cartilage in biolubrication. By providing an overview of recent approaches in manipulating the tribological properties of various polymeric surfaces, this review aims to encourage the fabrication of sustainable lubricating materials with low coefficient of friction and high wear resistance. Graphical abstract: Image, graphical abstract